Protection for Land Right Holders Used In Economic Area Development in Praya - Fitriana Maghfirah; Fully Handayani (Budapest International Research and Critics University, 2022)
In Central Lombok there are problems regarding the Development of Special Economic Zones located in Pujut District, Praya, Central Lombok. The project was carried out by PT. X with an area of 1,035.67 Ha and facing the Indian Ocean, the project is expected to grow potential and explore more about the tourism sector in West Nusa Tenggara Province. This research aims to describe or provide an overview of legal protections for land rights holders and explain what obstacles are experienced in this study. This research uses an explanatory method which means that research is carried out to find answers to problems by examining legal sources that are related to the formulation of problems. Data collection techniques used by literature studies and interviews to corroborate the secondary data needed. The data analysis technique used is qualitative. The results obtained that legal protection that can be given to holders who have property rights in Kuta Village located in Central Lombok Regency, with problems regarding claims made by other parties in the development of special economic zones have been listed in the principle of national land law and Law No. 2 of 2012 concerning Land Procurement for Development for Public Interest so that there is a need for compensation for losses experienced fairly and appropriately. in accordance with the agreement of both parties so as to achieve equality in providing their respective views and desires. There are obstacles in the form that both parties cannot find a bright spot regarding the amount of compensation.